2008
DOI: 10.1111/j.1572-0241.2008.01865.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of Mortality From Nonvariceal Upper Gastrointestinal Hemorrhage: A Multicenter Study

Abstract: These results indicate that 30-day mortality for nonvariceal bleeding is low. Deaths occurred predominantly in elderly patients with severe comorbidities or those with failure of endoscopic intention to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
86
6
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 18 publications
16
86
6
3
Order By: Relevance
“…The number of comorbidities was significantly higher in patients who died and it was an independent predictor of death (OR: 1.6; 95% CI: 1-2.5, p = 0.045). This finding is similar to that observed in other studies, particularly RUGBE and PNED studies (3,5,8). On the other hand, hypovolemic shock as cause of death was significantly higher in patients without comorbidities than in those with comorbidities (48 vs. 21%, p = 0.02).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The number of comorbidities was significantly higher in patients who died and it was an independent predictor of death (OR: 1.6; 95% CI: 1-2.5, p = 0.045). This finding is similar to that observed in other studies, particularly RUGBE and PNED studies (3,5,8). On the other hand, hypovolemic shock as cause of death was significantly higher in patients without comorbidities than in those with comorbidities (48 vs. 21%, p = 0.02).…”
Section: Discussionsupporting
confidence: 91%
“…Current evidence sug- gests that early administration of PPIs is the standard treatment of patients with NVUGB (20)(21)(22)(23)(24). The rebleeding rate observed in our patients (3.4%) was similar to that observed in the Italian PNED study (3.2%) and in other recent publications (17,18), but it was significantly lower than that reported in the Canadian RUGBE study (14.1%) (3,5,8). The divergence of our results from the ones of the Canadian study may be explained because a higher proportion of our patients received combined endoscopic therapy (adrenaline injection plus BICAP) than in the Canadian study; combined therapy has been shown to be superior to pharmacologic treatment for reduction of rebleeding in controlled trials (25)(26)(27).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Predictors of in-hospital mortality among cirrhotic patients with NVUGIB in our study were bacterial infection during hospitalization, shock, early rebleeding, low serum albumin, low baseline hemoglobin, and endoscopic treatment, whereas the following predictors were observed in the non-cirrhotic patients: severity of a bleeding episode, functional class, in-hospital bleeding, number of comorbidities, and advanced age (2,12,21,24,25).…”
Section: Discussionmentioning
confidence: 53%
“…Upper gastrointestinal (GI) bleeding is a common lifethreatening condition with a reported mortality rate of 4%-15% in most studies (1)(2)(3)(4)(5). Upper GI bleeding is classified according to the presence of a variceal or nonvariceal source of bleeding.…”
Section: Introductionmentioning
confidence: 99%